Evaluasi Efektivitas Alokasi Anggaran Belanja Daerah 11 Prioritas Pembangunan Jawa Barat Tahun 2022 - Rustandi, Sheilla Destia Putri; Dahtiah, Neneng (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Effectiveness at the regional budget level is very important, because this is to determine the level of achievement of work program results with predetermined targets. The purpose of this research is to analyze how the Effectiveness of Regional Expenditure Budget Allocation towards 11 Development Priorities of West Java. The analytical method used is a quantitative descriptive method, namely by establishing the concept of calculating financial ratios from the realization of the budget contained in the West Java Government Budget Realization Report. The data source used in this study is only secondary data obtained from the Budget Realization Report of West Java Province. The secondary data used is data documentation in the form of information in the form of books, archives, documents, writings, numbers and pictures in the form of reports and information that can support research. The results of the research show that the allocation of regional spending for 11 development priorities in West Java in 2022 is effective in its implementation through infrastructure development programs and activities.